Effect of Video Type on the Intention to Follow the Influencer's Advice on Tik Tok: Moderating Role of the Need for Humor - Chaabane, Khouloud; Rym Bouzaabia (Journal of Digital Marketing and Communication, 2025)
In a context characterized by a strong and increasing competitiveness of digital markets, it was essential to understand how humor could increase the intention of followers on Tik Tok. This study fills a gap in previous research by examining the effect of the types of videos (humorous vs non-humorous) on the attitude towards the influencer and the intention to follow the influencer's advice.  A quantitative approach was adopted, and an online questionnaire was distributed to Tik Tok followers. The sample, consisting of 120 followers of a popular TikTok influencer, was analyzed using the SPSS and AMOS 23 software. To test the hypotheses, we used means comparison tests, supplemented by a moderation mediation analysis using model 7 of the Hayes macro PROCESS. The results of a quasi-experiment showed that the humorous video increases the attitude towards the influencer more than the non-humorous video. In addition, the results show that the attitude towards the influencer positively influences the intention to follow the influencers' advice. On the other hand, the results revealed that the moderating role of the need for humor is confirmed. These results enrich the understanding of the mechanisms by which humor influences TikTok followers in search of more captivating experiences. It would be relevant for subsequent research to reproduce the study by mobilizing a larger sample, so as to strengthen the reliability and generalization of the conclusions and to integrate additional variables to enrich the current model.